Percutaneous Gastronomy and Jejunostomy: Lessons from the First Decade - John S Goff (Canadian Journal of Gastroenterology)
Percutaneous gastrostomies and jejunostomies have increasingly been used for long term enteral feeding in patients with functioning gastrointestinal tracts but who are unable, for a variety of reasons, to use the standard oropharyngeal route. Since these devices can be placed without the use of general anesthesia, the morbidity and mortality generally are less than for placement of a surgical gastrostomy. A permanent gastrostomy tube is easy to manage in most patients who require prolonged tube feeding. There are four basic types of percutaneous gastrostomy techniques; three employ an endoscope and one uses only radiographic or ultrasonic guidance. All gastrostomy tubes may be convened to feeding jejunostomies if the clinical situation warrants. Jejunal feeding tubes are prone to many technical problems and do not always solve the problems of gastric dysfunction and reflux that make gastrostomy tubes less desireable. Percutaneous endoscopic gastrostomics are technically simple to perform and have become the main method for access to the gastrointestinal tract in many patients. If judiciously used, the percutaneous enterostomy offers many benefits over a nasogastric tube for long term enteral feeding.